Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Kelas II Tema 5 Subtema 4 di SD N 1 Sidodadi Kecamatan Patean Kabupaten Kendal - Yuliyanti, Nisrina Arum; Mushafanah, Qoriati; Handayani, Diana Endah (Pena Edukasia, 2023)
The background of the problem in this study is that it is known that the empowerment of problem solving skills is not optimal. During the learning process, the teacher has not brought up the phenomena that occur related to the material to find a solution. Such a learning process has not led students to a problem that requires students to be able to formulate problems, formulate hypotheses, collect data, test hypotheses, draw conclusions, and recommend problem solutions. This type of research is quantitative research with the type of experimental research method and using the One-Group Pretest-Posttest design. From the t test analysis data obtained t count = 1.07143 then compared with t table = 2.13 with db = 15-1 at a significant level of 5%. The results show t count > t table, then H0 is rejected and Ha is accepted. From the results obtained, it can be said that learning Theme 5 Sub-theme 4 using the Problem Based Learning model affects the learning outcomes of class II students and can improve the learning outcomes of class II students at SDN 1 Sidodadi.